Polymicrobial Nature of Tick-Borne Diseases - Santiago Sanchez-Vicente (American Society for Microbiology, 2019)
ABSTRACT Tick-borne diseases have doubled in the last 12 years, and their geographic distribution has spread as well. The clinical spectrum of tick-borne diseases can range from asymptomatic to fatal infections, with a disproportionate incidence in children and the elderly. In the last few years, new agents have been discovered, and genetic changes have helped in the spread of pathogens and ticks. Polymicrobial infections, mostly in Ixodes scapularis, can complicate diagnostics and augment disease severity. Amblyomma americanum ticks have expanded their range, resulting in a dynamic and complex situation, possibly fueled by climate change. To document these changes, using molecular biology strategies for pathogen detection, an assessment of 12 microbes (9 pathogens and 3 symbionts) in three species of ticks was done in Suffolk County, New York. At least one agent was detected in 63% of I. scapularis ticks. Borrelia burgdorferi was the most prevalent pathogen (57% in adults; 27% in nymphs), followed by Babesia microti (14% in adults; 15% in nymphs), Anaplasma phagocytophilum (14% in adults; 2% in nymphs), Borrelia miyamotoi (3% in adults), and Powassan virus (2% in adults). Polymicrobial infections were detected in 22% of I. scapularis ticks, with coinfections of B. burgdorferi and B. microti (9%) and of B. burgdorferi and A. phagocytophilum (7%). Three Ehrlichia species were detected in 4% of A. americanum ticks. The rickettsiae constituted the largest prokaryotic biomass of all the ticks tested and included Rickettsia amblyommatis, Rickettsia buchneri, and Rickettsia montanensis. The high rates of polymicrobial infection in ticks present an opportunity to study the biological interrelationships of pathogens and their vectors. IMPORTANCE Tick-borne diseases have increased in prevalence in the United States and abroad. The reasons for these increases are multifactorial, but climate change is likely to be a major factor. One of the main features of the increase is the geographic expansion of tick vectors, notably Amblyomma americanum, which has brought new pathogens to new areas. The clinical spectrum of tick-borne diseases can range from asymptomatic to fatal infections, with a disproportionate incidence in children and the elderly. In addition, new pathogens that are cotransmitted by Ixodes scapularis have been discovered and have led to difficult diagnoses and to disease severity. Of these, Borrelia burgdorferi, the agent of Lyme disease, continues to be the most frequently transmitted pathogen. However, Babesia microti, Borrelia miyamotoi (another spirochete), Anaplasma phagocytophilum, and Powassan virus are frequent cotransmitted agents. Polymicrobial infection has important consequences for the diagnosis and management of tick-borne diseases.